THE USE OF INSTAGRAM ON THE POLITICAL PREFERENCES OF NOVICE VOTERS IN THE 2024 PRESIDENTIAL ELECTION IN THE SOUTHERN TAMBUN SUB-DISTRICT - Amelia, Dita; Mustika Kartika Sari (Kajian Moral dan Kewarganegaraan, 2024)
This study aims to examine the political preferences of novice voters related to the use of Instagram in the 2024 Presidential Election in South Tambun District. The focus of this research is how the intensity of Instagram use, consistency of access, and variety of content can affect the tendency of voters to vote or not vote. This research uses a descriptive quantitative method through a survey of 100 respondents of novice voters aged 17-25 years in South Tambun District. The data in the study were collected through an online questionnaire and then analyzed using descriptive analysis techniques. This research was conducted based on the phenomenon that occurred in the 2024 Presidential Election, namely the high involvement of novice voters, because they accounted for 55% of the total registered voters, exceeding half of the total number of permanent voter lists. The results showed that respondents' political preferences were evenly split, with 50% of respondents tending to exercise their right to vote, while the other 50% chose not to participate in the 2024 Presidential Election. The variety of content on Instagram proved to be a major factor that can influence voters' political decisions, with 76% of respondents who use Instagram sticking to their initial choice, while 24% changed their choice after being exposed to political content. In addition, 86% of voters who initially did not intend to vote eventually decided to participate after being exposed to content on Instagram. The conclusion of this study is that Instagram plays a role in facilitating the formation and change of political preferences among first-time voters, making it an effective platform for candidates and political parties to reach young voters in the digital age.